Kontribusi Kepemimpinan Kepala Sekolah, Motivasi Kerja,dan Iklim Sekolah terhadap Kinerja Guru - Subandi, Subandi (Universitas Pendidikan Ganesha, 2017)
This study aims at determining the contribution of school principal leadership, work motivation and school climate to the performance of elementary school teachers at Cluster IV District of Baturiti Tabanan Bali. This research was an ex-post facto research. The population which as also treated as the sample in this study were 61 teachers. Data in this study were collected by using questionnaires. Data analysis was performed by using simple regression, multiple regression, and partial correlation. The results showed that: (1) there was a significant contribution of headmaster leadership to the performance of elementary school teachers, (2) ) there is a significant contribution of teacher's work motivation to the performance of elementary school teacher; (3) there is significant contribution of work climate on the performance of elementary school teachers, and (4) together, there is a significant contribution of principal leadership, motivation work and work climate on the performance of elementary school teachers.